Spinach consumption ameliorates the gut microbiota and dislipaemia in rats with diet-induced non-alcoholic fatty liver disease (NAFLD). Issue 4 (2nd April 2019) - Elvira-Torales, L. I.; Periago, M. J.; González-Barrio, R.; Hidalgo, N.; Navarro-González, I.; Gómez-Gallego, C.; Masuero, D.; Soini, E.; Vrhovsek, U.; García-Alonso, F. J.
Abstract : In rats with hepatic steatosis, spinach intake increased gut Lactobacillus and lowered cholesterol and glucose. Abstract : Non-alcoholic fatty liver disease (NAFLD) is defined as the accumulation of fat in liver cells, which causes serious health consequences. Animal and human studies suggest that the gut microbiota plays a role in the pathogenesis of NAFLD. Here, we investigated whether spinach consumption could ameliorate high-fat-diet-induced disturbances in certain intestinal bacterial groups and products derived from their metabolism, such as short-chain fatty acids (SCFAs) and microbial phenolic catabolites. Attention is also paid to blood lipids and glucose. In the study, a rat model of high-fat-diet-induced NAFLD was used. There were six experimental groups: NC (normal diet), NB (normal diet + 2.5% spinach), NA (normal diet + 5% spinach), HC (high-fat diet), HB (high-fat diet + 2.5% spinach) and HA (high-fat diet + 5% spinach). The rats consumed these diets for five weeks, and after that, they were sacrificed and plasma, urine, intestinal content, faeces and liver samples were taken. Biochemical parameters were analyzed in plasma, phenolic catabolites were quantified in the faeces, urine, plasma and liver by UPLC-ESI-MS/MS, and the analysis of the microbiota and SCFAs in the intestinal content was performed by qPCR and GLC. Consumption of a high-fat diet caused NAFLD and dislipaemia and altered the gut microbiota and the pattern of SCFAs and phenolic gut microbial catabolites. Supplementation with spinach partially ameliorated some alterations induced by the high-fat diet, in particular by increasing the Lactobacillus counts, reducing the fasting glucose and total and LDL-cholesterol and preventing excess liver cholesterol accumulation, thereby improving the values of the steatosis biomarkers.